2018
DOI: 10.1016/j.scitotenv.2017.12.130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of how contaminants arise in a dredged marine sediment and analysis of the effect of natural weathering

Abstract: Millions of tons of contaminated sediments are dredged each year from the main harbors in France. When removed from water, these sediments are very reactive, therefore their geochemical behavior must be understood in order to avoid dispersion of contaminated lixiviates in the surrounding soils. In this objective, it is necessary to evaluate the principal physicochemical parameters, and also achieve advanced mineralogical characterization. These studied sediments are highly contaminated by metals, notably coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…By contrast, studies on marine sediment cores collected from the Palos Verdes Shelf (California, USA), where municipal wastes had been deposited for about 45 years, showed no indication of PCB transformation by diagenetic processes (Eganhouse et al, 2000). Furthermore, in a study on weathering of marine sediments stored for 5 years in an outdoor environment after dredging, Couvidat et al (2018) showed that concentrations of PCBs remained constant, whereas the concentrations of other organic pollutants, such as polycyclic aromatic hydrocarbons and organotin compounds substantially decreased. Hence under favorable sedimentary conditions, environmental records of PCBs may remain stable for many decades and possibly centuries.…”
Section: Characteristics and Environmental Fate Of Pcbsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, studies on marine sediment cores collected from the Palos Verdes Shelf (California, USA), where municipal wastes had been deposited for about 45 years, showed no indication of PCB transformation by diagenetic processes (Eganhouse et al, 2000). Furthermore, in a study on weathering of marine sediments stored for 5 years in an outdoor environment after dredging, Couvidat et al (2018) showed that concentrations of PCBs remained constant, whereas the concentrations of other organic pollutants, such as polycyclic aromatic hydrocarbons and organotin compounds substantially decreased. Hence under favorable sedimentary conditions, environmental records of PCBs may remain stable for many decades and possibly centuries.…”
Section: Characteristics and Environmental Fate Of Pcbsmentioning
confidence: 99%
“…Furthermore, in a study on weathering of marine sediments stored for 5 years in an outdoor environment after dredging, Couvidat et al (2018) showed that concentrations of PCBs remained constant whereas the concentrations of other organic pollutants, such as polycyclic aromatic hydrocarbons and organotin compounds substantially decreased. Hence under favorable sedimentary conditions, environmental records of PCBs may remain stable for many decades and possibly centuries.…”
Section: Stability and Transformations Of Pcbs In Environmental Archivesmentioning
confidence: 99%
“…For this these reasons, contaminated sediments need to be properly managed to eliminate risk of contamination. Sediments dredging before their stabilization and/or revalorization is widely used for contaminated sediments management [3][4][5][6][7]. However, sediments dredging changes their environmental conditions in terms of temperature, humidity, redox potential, grain accessibility by oxidizing agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the calcination of the sludge only generates water vapor [12]. As a result, some researchers have partially replaced Portland cement in concrete with calcinated sludge [13,14]. In the cement industry, the recent research of sludge vaporization mainly characterizes physical, chemical, mineralogical, and sustainability features.…”
Section: Introductionmentioning
confidence: 99%